IMPLEMENTASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR NEGERI 001 PASAR LUBUK JAMBI - Vivin Ramadana; Bustanur Bustanur; Sopiatun Nahwiyah (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
The values of Islamic religious education need to be implemented or internalized to students starting from an early age, including in elementary schools. So that in the future they have good morals in accordance with the existing Islamic values. For this reason, in thematic learning, teachers should teach or familiarize students with Islamic values that are based on the Qur'an and Hadith. This study aims to describe the values of Islamic religious education in thematic learning at 001 Pasar Lubuk Jambi Primary School. This type of research is qualitative with a qualitative descriptive design. Data collection techniques used were interviews, observation and documentation. Data analysis uses active analysis according to Miles and Huberman namely data reduction, data display and conclusion drawing. The validity of the data uses triagulation techniques and sources. The results showed that the implementation of Islamic religious education values in thematic learning in class V of theState Elementary School 001 Pasar Lubuk Jambi had appeared although not yet running optimally because the values of Islamic education implemented were still of a general nature such as reading prayers before and after learning.